Keanekaragaman Spesies Parasitoid Telur Hama Lepidoptera dan Parasitisasinya pada Beberapa Tanaman di Kabupaten Solok, Sumatera Barat - Hidrayani, Hidrayani; Rusli, R.; Lubis, Y. S. (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
A study was conducted to determine the species diversity of lepidoptera egg parasitoids on several crops in Solok. lepidopteran eggs were collected from rice, corn, tomato, and cabbage. A survey was conducted by using Stratified Purposive Sampling Method. Two districts (Gunung Talang and Lembah Gumanti) were chosen as centre of the target crops. The results showed that five species of egg parasitoids were found parasitizing lepidopteran eggs. The species found on rice were Telenomus sp., Tetrastichus sp., and Trichogramma japonicum parasitizing Scirpophaga incertulas and Hesperiidae with parasitization levels were 29.54; 13.02; and 2.05% respectively. The species found on corn was Trichogrammatoidea spp. parasitizing Helicoverpa armigera with parasitization level was 29.07%. None of parasitoid was found to parasitize eggs of H. armigera on tomato. The egg parasitoid parasitizing Crocidolomia pavonana and Spodoptera litura on cabbage was Trichogramma chilotrae with parasitization level was 1.67%. The most abundance species of lepidopteran egg parasitoids were Telenomus sp.and Trichogrammatoidea sp. The diversity index of egg parasitoids on rice in different sample areas varied from 0.46 to 0.63 based on Simpsons index. It indicated that the species diversity of lepidopteran eggs was relatively low.